Two typical phases of failure acceleration in rocks under uniaxial compression - Cheng, L.; Hao, S.; Lu, Chunsheng; Zhou, S. (2024)
The critical power-law acceleration of response quantities has been widely accepted and validated as an effective way to predict the failure time. However, in practical applications, only the data in the vicinity of the failure time exhibit critical power-law behaviour, which cannot describe the entire acceleration stage. In this study, it is shown that by using experimental results from the catastrophic failure of rocks under uniaxial compression, the acceleration of the mean strain presents two typical phases, and the final data in close proximity to the catastrophic time conform to the critical power-law trend. The early part of the acceleration stage is dominated by an exponential relationship with time to failure. Thus, the entire acceleration stage can be described using a combination of exponential and power-law functions. A prediction method based on a combined description of the entire acceleration failure process is proposed to forecast the failure time and is validated by experimental results. This combined description allows for an earlier warning of catastrophic failure than the power-law alone.